Endocrine disrupting metals lead to alteration in the gonadal hormone levels in Nigerian e-waste workers - Igharo, Osaretin Godwin; Anetor, John I; Osibanjo, Oladele; Osadolor, Humphrey Benedo; Odazie, Emmanuel C; Uche, Zedech Chukwuemelie (Universa Medicina, 2018)
BACKGROUNDElectronic waste (e-waste) is known to contain thousands of toxic chemicals and metals, many of which have identified endocrine disruption potentials even at low blood concentrations resulting from occupational and environmental exposures. E-waste crude reprocessing in Nigeria is massive and a growing number of Nigerians are occupationally exposed. The present study aimed to determine changes in gonadal hormone levels associated with occupational crude e-waste reprocessing in Nigerian male e-waste workers. METHODSThis cross-sectional study which was carried out in Benin City, South-South Nigeria recruited male e-waste workers (n=63); and apparently healthy non e-waste workers (n=41), as exposed and unexposed participants respectively. Male fertility hormones which includes luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone (TESTO) and prolactin (PROL); as well as progesterone (PROG), estrogen (EST) and inhibin (INH) were determined using enzyme linked immunosorbent assay (ELISA) methods; whole blood levels of chromium, cadmium, arsenic and mercury were determined using Inductively Coupled Plasma Mass Spectrometry. RESULTSLevels of TESTO, PROG, LH and FSH; as well as PROL and EST were significantly lower in e-waste workers compared with unexposed participants (p<0.05). In contrast, serum INH was significantly higher in e-waste exposed population compared with the unexposed. In addition, chromium correlated significantly and negatively with testosterone, progesterone and estrogen, while inhibin correlated positively with chromium. Similar correlation patterns were observed for cadmium, arsenic and mercury. CONCLUSIONNigerian e-waste workers experienced reduced levels of key gonadal hormones and this may be associated with occupational exposure to endocrine disrupting metals in e-waste.